University of Stellenbosch Legal Aid Clinic v Minister of Justice and Correctional Services : proactive judicial application of principle 3 of the G20 High Level Principles of Financial Consumer Protection - Brits, Reghard (University of Pretoria, 2019)
Mini Dissertation (LLM)--University of Pretoria, 2018.